Access to media and HIV knowledge in India - Smriti Agarwal; Pedro de Araujo (Economies, 2014)
This paper aims to better understand the relationship between HIV knowledge and media exposure in India. We use a two-stage hurdle model to estimate the effect of media sources such as newspapers, radios and television on AIDS-related knowledge among Indian men and women using demographic health survey data. Overall, access to newspapers, radio, or television increases the likelihood of better HIV knowledge in both males and females by an order between 2% and 12%. These findings, albeit quantitatively small, suggest, even if indirectly, possible problems faced by AIDS campaigns and government programs in combating the HIV epidemic in India.
Keywords: O12; O53; 330; HIV/AIDS; ordered probit; average partial effects; India